Integrated Guidelines for Growth and Jobs, 2005-2008: A Shift in EU Economic Policy? - Marica Frangakis (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2006)
First paragraph: The 2005 Broad Economic Policy Guidelines (BEPGs) are part of a broader policy package that also includes the Employment Guidelines pertaining to the four-year period 2005 to 2008. The two sets of guidelines constitute the »Integrated Guidelines for Growth and Jobs« which were endorsed by the European Council in June 2005. The Integrated Guidelines further represent the culmination of two review processes which were concluded by the European Council in March 2005, namely the review of the Lisbon Agenda and the reform of the Stability and Growth Pact (SGP). These were largely prompted by the continuing underperformance of the EU-15 making the attainment of the Lisbon objectives by 2010 unlikely. Th erefore, in order to gain an insight into the new Guidelines, it is necessary to discuss both the changes that have been made to the Lisbon Agenda and the SGP as well as to take a closer look at macroeconomic developments in Europe over the period 2005 – 2005.
Keywords: 330